Floppy's phonics book 11. Stage 2, Oxford Reading Tree Phonics: : revise and stretch - Hunt, Roderick; Brychta, Alex (OXFORD UK, 2011)
Level 2 Floppy's Phonics Sounds and Letters Books show all the sounds and graphemes from Phase 3 of Letters and Sounds in the context of Oxford Reading Tree scenes, packed with activities for practice and consolidation.